And We Met… - Bandellu, Neelima Jadhav (Nidān, 2021)
It was 1973. There was a horrifying drought in Maharashtra. No rains, no grains… Even to fetch drinking water, women had to walk miles together with no guarantee of returning with even half a pot of water. In such horrible times, Gail Omvedt, a young girl with blue eyes, blonde hair and a guitar in her hand and I met at the Lal Nishan Party office (Communist Party Office) for the very first time with my father Bhaskar-rao Jadhav. Senior comrades of LNP welcomed her to a small office. It was above a small hotel. The office had oily chairs and overhead was a hot tin roof. The place was surrounded by old temples of many Hindu gods. Though full of old dusty files, red flags scattered around and the crowd of workers, landless labourers, sanitary workers rushing in and out, the place strangely attracted Gail. The hot flames from the stove of the hotel below heated up the walls and the floor of the office. Even then she looked pretty much at ease. Senior comrades of LNP - Datta Deshmukh, Santaram Patil, Madhukar Katre, Suresh Gawali and Bhaskar-rao Jadhav welcomed her. My father believed that social life and family life go hand-in-hand. So, every visitor of LNP stayed at our place. Gail was no exception. After her stay with us, we remained friends throughout our life till she gave her body to this soil.